(3WHbGJ GdMfGHdIs - (3GHf CHj jYdj , eMeO Hf eMeO Hf GdMSjf Hf eMeO GHf GdaQGQ, CHh GdMSjf,J (B526 (3g` s ((3YHOGdOGje Hf YHOGdLdjd Hf eMeO Hf YeQ Hf jbhH s)
(3ChdgG (B:s
(3GdMeO ddg dYdi GdYXje GdSejY GdHUjQ gPG cJGH GSJZQfG Gdg JYGdi ai JCdjag s
(3GfXQ GdbSe GdChd HQbe (B307s
(3HChdgG hBNQgG eWGdYGJ hJedcGJ HNW cKjQ ef TjhN GdMfGHdIs
(3fSNI LRCf ai eLdOjfs
(3fSNI QGHYI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdJGQjNs